Characterizing Global Investors' Risk Appetite for Emerging Market Debt During Financial Crises - Gonzalez-Hermosillo, Brenda (IMF Working Papers; Working Paper ;, 2003)
The effects of unanticipated movements in global risk on nine emerging bond markets are investigated. The components of global risk are volatility, credit, and liquidity risks. Country and contagion risks are also studied individually. A historical decomposition of bond spreads is used to identify the relative contributions of risk during 1998-99. The empirical results show that the Russian/LTCM crises were characterized by increases in global credit risk, while the relative size of global risk factors was mixed for the Brazilian crisis, with no component dominating. Country risk is found to be important for all countries, while there is little evidence of contagion risk.